2010
DOI: 10.1186/1471-2229-10-218
|View full text |Cite
|
Sign up to set email alerts
|

Production of haploids and doubled haploids in oil palm

Abstract: BackgroundOil palm is the world's most productive oil-food crop despite yielding well below its theoretical maximum. This maximum could be approached with the introduction of elite F1 varieties. The development of such elite lines has thus far been prevented by difficulties in generating homozygous parental types for F1 generation.ResultsHere we present the first high-throughput screen to identify spontaneously-formed haploid (H) and doubled haploid (DH) palms. We secured over 1,000 Hs and one DH from genetica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 32 publications
0
11
0
1
Order By: Relevance
“…Thanks to the knowledge of the oil palm gene space (Low et al, 2014), meiosis regulators, such as DMC1orthologs (Wijnker et al, 2012) can be identified and then controlled. The frequencies of spontaneous haploids in seed progeny are very low, 1,100 haploids among 60 million seedlings (Dunwell et al, 2010). Cultures of oil palm microspores have not yielded doubled-haploids so far (Corley and Tinker, 2003).…”
Section: Increasing Oil Palm Productivitymentioning
confidence: 99%
“…Thanks to the knowledge of the oil palm gene space (Low et al, 2014), meiosis regulators, such as DMC1orthologs (Wijnker et al, 2012) can be identified and then controlled. The frequencies of spontaneous haploids in seed progeny are very low, 1,100 haploids among 60 million seedlings (Dunwell et al, 2010). Cultures of oil palm microspores have not yielded doubled-haploids so far (Corley and Tinker, 2003).…”
Section: Increasing Oil Palm Productivitymentioning
confidence: 99%
“…Population molecular diversity studies for breeding heterotic population organization, germplasm prospection and core collection which facilitate the selection, maintenance and exploitation of key genotypes and populations have also now become standard practice in many oil palm breeding programs [31,32,33,34]. Related to these are also homozygosity testing which expedites development of inbred (also isogenic and recombinant inbred lines) via single seed descent or doubled haploidy [15,35].…”
Section: Dna Marker or Molecular Marker-assisted Breeding (Mab)mentioning
confidence: 99%
“…Penggunaan varietas unggul kelapa sawit hibrida merupakan komponen terpenting dalam lonjakan peningkatan produktivitas kelapa sawit (Dunwell et al, 2010). Sampai dengan 2016, terdapat 11 produsen benih kelapa sawit di Indonesia.…”
Section: Pendahuluanunclassified